THE GROUND-STATE ENERGY OF AN EXCITON IN A PARABOLIC QUANTUM-DOT - ELSAID, M (Iop Publishing Ltd, 1994)
The shifted 1/N expansion method is used to solve the-effective-mass Hamiltonian for an interacting electron-hole pair in a quantum dot. The ground-state energy of an exciton parabolically confined in a quantum dot as a function of quantum dot size is obtained. Comparison shows our results are in excellent agreement with those of Que.
Keywords: Shifted 1/N Expansion; Potentials; Boxes